2003
DOI: 10.1152/ajplung.00226.2003
|View full text |Cite
|
Sign up to set email alerts
|

Chondroitin sulfate proteoglycans are required for lung growth and morphogenesis in vitro

Abstract: . Chondroitin sulfate proteoglycans are required for lung growth and morphogenesis in vitro. Am J Physiol Lung Cell Mol Physiol 285: L1323-L1336, 2003. First published August 15, 2003 10.1152/ajplung.00226. 2003 have been shown to play a key role in the development of many tissues. We have investigated the role of sulfated PGs in early rat lung development by treating cultured tissues with 30 mM sodium chlorate, a global inhibitor of PG sulfation. Chlorate treatment disrupted growth and branching of embryon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 76 publications
(76 reference statements)
1
40
0
Order By: Relevance
“…More recently, it has been shown that both heparan sulfate and chondroitin sulfate proteoglycans are required for lung branching and in fact mediate the inductive effects of FGF10 binding to the epithelium (93)(94)(95).…”
Section: Proteoglycansmentioning
confidence: 99%
“…More recently, it has been shown that both heparan sulfate and chondroitin sulfate proteoglycans are required for lung branching and in fact mediate the inductive effects of FGF10 binding to the epithelium (93)(94)(95).…”
Section: Proteoglycansmentioning
confidence: 99%
“…FGF7, which is produced by lung mesenchymal cells, is a potent mitogen for lung epithelial cells, both in vivo (Ulich et al, 1994;Simonet et al, 1995;Tichelaar et al, 2000) and in vitro (Shiratori et al, 1996;Bellusci et al, 1997;Cardoso et al, 1997;Shannon et al, 1999), as well as a strong inducer of alveolar type II cell differentiation (Chelly et al, 1999;Shannon et al, 1999). The differences in response of the lung epithelium to FGF10 and FGF7, even though both ligands signal primarily through FGFR2b, may be due to differential interactions with low-affinity proteoglycan coreceptors (Izvolsky et al, 2003;Shannon et al, 2003;Sedita et al, 2004). The differential response of epithelium to FGF10 and FGF7 is not limited to the lung.…”
Section: Su5402 Down-regulates Fgfsensitive Genes In the Lung Epitheliummentioning
confidence: 99%
“…PGs are also thought to act as a reservoir for growth factor binding and regulate cell migration, as well as cell-cell and cell-matrix binding. Recent evidence indicates that CS-PGs play a critical role in the early growth and branching morphogenesis of the lung (26).…”
mentioning
confidence: 99%